2022
DOI: 10.1186/s12951-022-01532-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro magnetosome remineralization for silver-magnetite hybrid magnetosome biosynthesis and used for healing of the infected wound

Abstract: Background Magnetosomes (BMPs) are organelles of magnetotactic bacteria (MTB) that are responsible for mineralizing iron to form magnetite. In addition, BMP is an ideal biomaterial that is widely used in bio- and nano-technological applications, such as drug delivery, tumor detection and therapy, and immunodetection. The use of BMPs to create multifunctional nanocomposites would further expand the range of their applications. Results In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…These cavities release mechanical energy that physically disintegrates cell components. Ultrasonic crushing has been applied in different works for BMN isolation [ 3 , 79 ]. However, the scalability of this operation is difficult because of the high energy consumption [ 78 ] and occupational inconvenience involved, as the sound waves released can damage audition without proper protective equipment.…”
Section: Bmn Purification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These cavities release mechanical energy that physically disintegrates cell components. Ultrasonic crushing has been applied in different works for BMN isolation [ 3 , 79 ]. However, the scalability of this operation is difficult because of the high energy consumption [ 78 ] and occupational inconvenience involved, as the sound waves released can damage audition without proper protective equipment.…”
Section: Bmn Purification Methodsmentioning
confidence: 99%
“…Notably, under metal-rich environments, bacterial growth can be greatly hindered, highlighting the importance of understanding the growth of the metabolism of MTB considering their application in bioremediation. Recently, it was shown that purified BMNs also can incorporate metals within their membranes [ 79 ]. The ability to re-mineralize and incorporate metals into the BMN crystal may be useful for bioremediation purposes and generate BMNs with different compositions and features.…”
Section: Functionalization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These issues could be potentially addressed through the replacement of magnetic nanomaterials with magnetotactic bacteria, which are gram-negative bacteria that correlate their directional movement with the direction of an applied magnetic field. Currently, among the 11 magnetotactic bacteria that have been isolated and purified, of which Magnetospirillum gryphiswaldense MSR-1 is the most studied as a model strain. Magnetotactic bacteria have the ability to absorb iron ions in the environment and accumulate these ions as magnetite (Fe 3 O 4 ), pyropyrite (F 3 S 4 ), or tetragonal pyrite (FeS) crystal particles in prokaryotic organelles denoted as magnetosomes (MN), which are coated with lipid bilayer membranes or biofilms in the bacteria cells . Of particular importance in the current context is that, compared with the chemically synthesized magnetic nanoparticles, the MN are small, uniform, difficult to aggregate, and nontoxic.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular importance in the current context is that, compared with the chemically synthesized magnetic nanoparticles, the MN are small, uniform, difficult to aggregate, and nontoxic. Most importantly, the biofilms on the surfaces of MN include a large number of bioactive groups, such as amino, carboxyl, free fatty acids, sugars, and phospholipids, that can be used as targets for connecting with selected compounds, thereby facilitating the modification of MN with various antibodies, enzymes, nucleic acids, chemotherapy drugs, and metal ions. As a result, MN have been widely used in tumor chemotherapy, drug delivery, and immunoassay applications. , However, MN have rarely been considered for use in food.…”
Section: Introductionmentioning
confidence: 99%